Igf2/H19 Imprinting Control Region (ICR): An Insulator or a Position-Dependent Silencer? - Subhasis Banerjee; Alan Smallwood; Scott Lamond; Stuart Campbell; Geeta Nargund (The Scientific World Journal)
The imprinting control region (ICR) located far upstream of the H19 gene, in conjunction with enhancers, modulates the transcription of Igf2 and H19 genes in an allele-specific manner. On paternal inheritance, the methylated ICR silences the H19 gene and indirectly facilitates transcription from the distant Igf2 promoter, whereas on the maternal chromosome the unmethylated ICR, together with enhancers, activates transcription of the H19 gene and thereby contributes to the repression of Igf2. This repression of maternal Igf2 has recently been postulated to be due to a chromatin boundary or insulator function of the unmethylated ICR. Central to the insulator model is the site-specific binding of a ubiquitous nuclear factor CTCF which exhibits remarkable flexibility in functioning as transcriptional activator or silencer. We suggest that the ICR positioned close to the enhancers in an episomal context might function as a transcriptional silencer by virtue of interaction of CTCF with its modifiers such as SIN3A and histone deacetylases. Furthermore, a localised folded chromatin structure resulting from juxtaposition of two disparate regulatory sequences (enhancer ICR) could be the mechanistic basis of ICR-mediated position-dependent (ICR-promoter) transcriptional repression in transgenic Drosophila.